Free-energy relationships for the interactions of tryptophan with phosphocholines - Blaser, Georg; Sanderson, John M.; Wilson, Mark R. (Organic & biomolecular chemistry, 2009)
In membrane proteins and peptides, tryptophan exhibits a marked tendency to occur in locations that correspond to the interfacial region of the lipid bilayer. The relative contributions of electrostatic, dipolar, hydrophobic and conformational effects on the interactions of tryptophan with lipids have been the subject of much speculation. In order to elucidate the fundamental properties of tryptophan-phosphocholine interactions in the absence of competing factors such as protein conformation and membrane perturbation, we have determined the binding characteristics of a homologous series of tryptophan analogues to 1,2-dimyristoyl-sn-glycero-3-phosphocholine (DMPC) in deuterochloroform using NMR titrimetric approaches. The data are analysed using a binding model that includes lipid aggregation and the explicit association of water with the lipid. For a series of substituents (OMe, Me, H, F, Cl, Br, I, NO(2)) at the 5-position of the indole ring, the trends in the free energy of association for the formation of 1 : 1 and 1 : 2 lipid-tryptophan adducts both follow an inverted- relationship as a function of the corresponding para-Hammett parameter, with tryptophan (R = H) exhibiting the weakest binding. These trends are shown to be consistent with participation of the indole side chain in both hydrogen bonds and cation-pi interactions. Molecular dynamics simulations of tryptophan and DMPC in an explicit chloroform solvent model demonstrate that for the formation of lipid-tryptophan adducts, binding is driven predominantly by carbonyl-cation and cation-pi interactions with the choline ammonium group, alongside hydrogen bonding interactions with the lipid phosphate. Some of these interactions operate co-operatively, which may account for the observed trends in free energy.